Impact of early brain lesions on the optic radiations in children with cerebral palsy - Araneda, Rodrigo; Ebner-Karestinos, Daniela; Dricot, Laurance; Herman, Enimie; Hatem, Samar M.; Friel, Kathleen M.; Gordon, Andrew M.; Bleyenheuft, Yannick (Frontiers in Neuroscience, 2022)
Due to their early brain lesion, children with unilateral spastic cerebral palsy (USCP) present important changes in brain gray and white matter, often manifested by perturbed sensorimotor functions. We predicted that type and side of the lesion could influence the integrity of white matter tracts. Using diffusion tensor imaging in 40 children with USCP, we investigated optic radiation (OR) characteristics: fractional anisotropy (FA), mean diffusivity (MD), axial diffusivity (AD) and radial diffusivity (RD). First, we compared the OR of the lesional and non-lesional hemisphere. Then we evaluated the impact of the brain lesion type (periventricular or cortico-subcortical) and side in the differences observed in the lesional and non-lesional OR. Additionally, we examined the relationship between OR characteristics and performance of a visuospatial attention task. We observed alterations in the OR of children with USCP on the lesional hemisphere compared with the non-lesional hemisphere in the FA, MD and RD. These differences were influenced by the type of lesion and by the side of the lesion. A correlation was also observed between FA, MD and RD and the visuospatial assessment mainly in children periventricular and right lesions. Our results indicate an important role of the timing and side of the lesion in the resulting features of these children’s OR and probably in the compensation resulting from neuroplastic changes.